Hubungan Antara Self-Regulated Learning dengan Motivasi Belajar Siswa SMA Hang Tuah 2 Sidoarjo pada Masa Pandemi - Prasetyo , Adi; Laili, Nurfi (Indonesian Journal Publisher, 2023)
This research was based on the phenomenon problem of motivation to learn experienced by students of SMA Hang Tuah 2 Sidoarjo. This study aims to determine the relationship between self-regulation learning and learning motivation in students of Sma Hang Tuah 2 Sidoarjo. This research is included in the type of quantitative research with a correlational approach. This research was conducted at SMA Hang Tuah 2 Sidoarjo, East Java. The population in this study was 400 students, so from calculations using the Krejcie Morgan formula, the sample used 196 students taken using a simple random sampling technique. Data collection in this study used two psychological scales, namely the self-regulated learning scale from the aspect of self-regulated learning developed by Dewi (2019) and obtained a reliability coefficient value of (α) 0.939 and a learning motivation scale from the aspect of learning motivation developed by Santiarini (2020) and a reliability coefficient value of (α) 0.835 was obtained. Data analysis in this study using Spearman's Correlations and this analysis process used the help of the JASP program version 0.14.0.0 for windows. The results of the study obtained a value of r = 0.538 and a p value = 0.001 where 0.001 < 0.05 which means that there is a positive relationship between self regulated learning variables and academic procrastination in students of SMA Hang Tuah 2 Sidoarjo.